1980
DOI: 10.1079/bjn19800095
|View full text |Cite
|
Sign up to set email alerts
|

The influence of molybdenum on the copper metabolism of the rat at different Cu levels of the diet

Abstract: 1.Male WAG/Cpb inbred rats fed on rations with approximately 1-5 rng copper/kg (deficient), 6.0 mg Cu/kg (adequate) and 25.0 mg Cu/kg (excess) were supplemented with varying amounts of molybdenum (0, 50, 150 and 500 mg/kg diet) and the effect on the Cu concentration of blood, plasma, liver and kidney, the caeruloplasmin activity of plasma and the Mo concentration of liver and kidney were studied.2. M o increased the Cu concentration of blood, plasma, liver and kidney and the Mo concentration of liver and kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…10 gm amount suggested byPauling (63). This study indicated that 1500 mg ascorbic acid daily over a relatively short period of time can significantly decrease copper status in healthy adult males.The results of this study call into question safety of prolonged self dosage of ascorbic acid at high levels.SUMMARYIntestinal absorption of copper has been found to be decreased in the presence of such factors as zinc,' molybdenum, cadmium and potassium sulfide(5)(6)(7)(8)(9). Findings from several animal studies indicate that ascorbic acid will also decrease intestinal copper absorption(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 gm amount suggested byPauling (63). This study indicated that 1500 mg ascorbic acid daily over a relatively short period of time can significantly decrease copper status in healthy adult males.The results of this study call into question safety of prolonged self dosage of ascorbic acid at high levels.SUMMARYIntestinal absorption of copper has been found to be decreased in the presence of such factors as zinc,' molybdenum, cadmium and potassium sulfide(5)(6)(7)(8)(9). Findings from several animal studies indicate that ascorbic acid will also decrease intestinal copper absorption(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…The effect of molybdenum may be due to its nonspecifically binding to sulfur compounds that are specific for copper(62). In the rat molybdenum was found to raise blood levels of molybdenum and copper when copper intake was adequate(9).…”
mentioning
confidence: 99%
“…Molybdenum (Mo), also an essential trace element, is found in enzymes such as xanthine oxidase (Schwarz et al 2009). The metabolism of these two essential elements is interrelated so that an increase in dietary Mo can interfere with the bioavailability of Cu (Nederbragt 1980). This may be due to a decrease in Cu absorption and/or interference by Mo with Cu utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the homeostasis of essential elements, especially zinc and copper, by toxic metals have been studied from the standpoint of understanding of the harmful action of the metals on the organism (1,2). Disturbances in the metabolism of endogenous metals may be induced in experimental animals by administration of cadmium (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), nickel (3,18,19), silver (18,(20)(21)(22), bismuth (23,24), gold (25,27), tin (28), molybdenum (29), and both inorganic mercury (22,23,26,(30)(31)(32) and methylmercury (31).…”
Section: Introductionmentioning
confidence: 99%